3D-STED Super-Resolution Microscopy Reveals Distinct Nanoscale Organization of the Hematopoietic Cell-Specific Lyn Substrate-1 (HS1) in Normal and Leukemic B Cells - Sampietro, Marta; Zamai, Moreno; Díaz Torres, Alfonsa; Labrador Cantarero, Veronica; Barbaglio, Federica; Scarfò, Lydia; Scielzo, Cristina; Caiolfa, Valeria R. (Frontiers in Cell and Developmental Biology, 2021)
HS1, the hematopoietic homolog of cortactin, acts as a versatile actin-binding protein in leucocytes. After phosphorylation, it is involved in GTPases and integrins activation, and in BCR, TCR, and CXCR4 downstream signalling. In normal and leukemic B cells, HS1 is a central cytoskeletal interactor and its phosphorylation and expression are prognostic factors in Chronic Lymphocytic Leukaemia (CLL) patients. We here introduce for the first time a super-resolution imaging study on primary CLL cells approach based on single cell 3D-STED microscopy optimized for revealing and comparing the nanoscale distribution of endogenous HS1 in healthy B and CLL cells. Our study reveals that the endogenous HS1 forms heterogeneous nanoclusters, similar to those of YFP-HS1 over-expressed in the leukemic MEC1 cell line. HS1 nanoclusters in healthy and leukemic B cells form bulky assemblies at the basal sides, suggesting the recruitment of HS1 for cell adhesion. This observation agrees with a phasor-FLIM-FRET and STED colocalization analyses of the endogenous MEC1-HS1, indicating an increased interaction with Vimentin at the cell adhesion sites. In CLL cells isolated from patients with poor prognosis we observed a larger accumulation of HS1 at the basal region and a higher density of HS1 nanoclusters in the central regions of the cells if compared to good prognosis CLL and healthy B cells, suggesting a different role for the protein in the cell types analysed. Our 3D-STED approach lays the ground for revealing tiny differences of HS1 distribution, its functionally active forms and colocalization with protein partners.